Charge redistribution of Ru nanoclusters on Co3O4 porous nanowire via the oxygen regulation for enhanced hydrogen evolution reaction. (July 2021) - Liu, Zhen; Zeng, Lili; Yu, Jiayuan; Yang, Linjing; Zhang, Jing; Zhang, Xiaoli; Han, Feng; Zhao, Lili; Li, Xiao; Liu, Hong; Zhou, Weijia
Abstract: Ru-based catalysts are widely studied for hydrogen evolution reaction. However, there is still a lack of research on which chemical environment is more favorable for the catalytic performance of Ru. In this work, Ru nanoclusters are loaded on porous Co3 O4 nanowires (Ru/Co3 O4 NWs), spherical aberration-corrected transmission electron microscope and extended X-ray absorption fine structure confirm the coordination environment of Ru with oxygen bond. Compare to Co nanowires, Ru/Co3 O4 NWs have the better HER performance in alkaline medium (an overpotential of 30.96 mV at a current density of 10 mA cm −2, electrochemical areas of 4.31 mF cm −2 ). Theoretical calculation also demonstrates the charge redistribution of Ru through the O binding, which has a smaller |ΔGH* | value. Besides, Ru clusters are loaded on Co foam and further oxygen doped to achieve efficient and stable HER activity. This work put a deep insight into the role of oxygen regulation of Ru-based HER catalysts. Graphical Abstract: ga1 Highlights: Ru/Co3 O4 NWs were synthesized through cation replacement and controlling reduction. The surrounding oxygen promoted the charge redistribution of Ru and enhanced its HER activity. This oxygen-enhanced strategy provided a cost-effective prospect of industrial application.